Experiential Learning in Circles of Safety: Reflections on Walls to Bridges and Dewey’s Theory of Experience (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2018)
This paper discusses a Winnipeg-based community-university partnership structured as a set of interlinked “Circles of Safety” to support criminalized women while incarcerated and after their release. The four Circles include university, community, social co-operatives, and corrections; these circles contain the action research activities we are undertaking to provide greater safety for women transitioning from prison into the community. The motivation for our prison education program, which draws on the American Inside-Out Program and the newer Canadian Walls to Bridges Program, comes from these four directions and is energized by a belief in the human right to education. This paper argues that the success of both American and Canadian programs is explained by an approach to prison education that is complementary to John Dewey’s principles of educative experience, specifically principles based on continuity and interaction. Adapting and extending Dewey, the Circles of Safety model described in this paper maintains the value of experiential learning, which is defined as learning in situations that begin with the experience that the learners already have and subject matter that is within the scope of their ordinary life-experience, leading to their formation of purpose.